Comparative study on information extraction of urban wetlands and its thermal environment using the SDGSAT-1 data - Liu, Linsong; Li, Qingyu; Niu, Zhenguo; Huo, Xuanlin (International journal of digital earth, 2024)
Wetlands represent crucial ecosystems, with urban wetlands playing a significant role in regulating regional thermal environments. The Sustainable Development Goals Scientific Satellite 1 (SDGSAT-1), equipped with multiple sensors, boasts one of the highest spatial resolutions among satellites housing thermal infrared sensors. A specific deep blue band, sensitive to chlorophyll in water, has been established, introducing innovative technological avenues for observing urban wetland environments. This study focuses on Beijing, investigating SDGSAT-1's efficacy in wetland classification and Land Surface Temperature (LST) retrieval, in comparison to Sentinel-2 and Landsat 8 TIRS data. The findings reveal that: (1) Wetland classification accuracy with SDGSAT-1 (86.76% overall accuracy, 0.84 Kappa coefficient, 0.87 Macro-F1) surpasses that of Sentinel-2, possibly attributed to the deep blue bands; (2) In contrast to Landsat 8's thermal infrared band, SDGSAT-1's finer resolution (30 m spatial resolution) offers more intricate spatial variation of LST, forming a foundational dataset for nuanced wetland thermal environment investigations; (3) The study underscores the comprehensive advantages of SDGSAT-1 data in monitoring urban wetlands and thermal environments, furnishing a theoretical basis for future related research.